1972
DOI: 10.2134/agronj1972.00021962006400040010x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rice Plants Grown in Three Potted Luzon Soils to Additions of Boron, Sulfur, and Zinc1

Abstract: Three low‐yielding Luzon soils, Quingua clay loam, Bantog loam, and Umingan loam, on which plants did not respond sufficiently to N, P, or K, were tested in pot studies with three levels of B, S, and Zn in a 34 factorial design to show the response on the yield and nutrient content of rice (Oryza sativa L.). None of the soils was deficient in B, as additions of B resulted in decreased yield and the development of foliar symptoms resembling those of B toxicity. Plants in two soils responded to the addition of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…L o c k a r d et al 15, have suggested that young rice plants may suffer from temporary deficiency duc to a higher zinc requirement during their early growth stages, and that enlargement of the root system may be a factor in their subsequen! L o c k a r d et al 15, have suggested that young rice plants may suffer from temporary deficiency duc to a higher zinc requirement during their early growth stages, and that enlargement of the root system may be a factor in their subsequen!…”
Section: Zinc Availability In Flooded Soilsmentioning
confidence: 99%
“…L o c k a r d et al 15, have suggested that young rice plants may suffer from temporary deficiency duc to a higher zinc requirement during their early growth stages, and that enlargement of the root system may be a factor in their subsequen! L o c k a r d et al 15, have suggested that young rice plants may suffer from temporary deficiency duc to a higher zinc requirement during their early growth stages, and that enlargement of the root system may be a factor in their subsequen!…”
Section: Zinc Availability In Flooded Soilsmentioning
confidence: 99%
“…Hydrogen sulfide, formed under submerged anaerobic conditions, induces iron toxicity, which prevails in rice-growing areas (Tanaka and Yoshida 1970). Nevertheless, sulfur deficiency in rice plants was observed in several countries; e.g., Bangladesh (Karim and Majlis 1958), Brazil (Wang 1979), India (Saran 1949), Indonesia (Ismunadji et al 1975), Myanmar (Aiyar 1945), and the Philippines (Lockard et al 1972). The deficiency is due mostly to a dilution effect caused by increasing yields associated with the intensive use of high-analysis fertilizers that contain little or no sulfur, and the exploitation of new lands in marginal areas.…”
mentioning
confidence: 99%